A Comprehensive Introduction to Sun Family Taiji Boxing: Theory and Applications - Burroughs, Jake (Revista de Artes Marciales Asiáticas, 2012)
Though well known in China, Sun Family Taiji is one of the least known of Chinese martial arts here in the West. Created by one of China’s top martial artists, Sun Lutang, in what many consider the “Golden Years” of Chinese pugilism (turn of the 20th century), this style offers proper structure, full body power, and dynamic stepping. Training in Sun Taiji presents not only an extremely healthy exercise for all ages, but also an effective system of combat. This is a concise yet inclusive overview of Sun Family Taiji Boxing, including the historical background, real-world applications, and the theory involved in this often overlooked system of Taiji.